2019
DOI: 10.1016/j.conb.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

What does the mind learn? A comparison of human and machine learning representations

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The advantage of AI is that it can deal with complex and data-rich problems stably and flexibly, which makes its application in medical bioinformatics take a qualitative leap [20,21]. In recent years, AI has shown higher accuracy in clinical prediction modeling of tumor genomics and is expected to become a promising tool for tumor diagnosis and prognosis evaluation [22,23]. Numerous research results have suggested that using artificial intelligence algorithm to construct multigene models based on RNA or protein levels has the indispensable clinical value of earlier diagnosis and prognosis estimation in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of AI is that it can deal with complex and data-rich problems stably and flexibly, which makes its application in medical bioinformatics take a qualitative leap [20,21]. In recent years, AI has shown higher accuracy in clinical prediction modeling of tumor genomics and is expected to become a promising tool for tumor diagnosis and prognosis evaluation [22,23]. Numerous research results have suggested that using artificial intelligence algorithm to construct multigene models based on RNA or protein levels has the indispensable clinical value of earlier diagnosis and prognosis estimation in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other constraints, such as representational or process noise constraints, are less well-attested and their consequences less clear cut. For example, applying representational constraints require first establishing what the representations are, and the nature of cognitive representations is often controversial (Spicer & Sanborn 2019).…”
Section: Sampling As a Resource-rational Constraintmentioning
confidence: 99%
“…In many cases, there is a lack of objective and effective evaluation indicators. Recent advances in computing power and big data handling has enabled some artificial intelligence applications began to outperform human intelligence in solving tasks that require complex decision-making ( 10 ). Common machine-learning algorithms include the support vector machine (SVM), random forest (RF), and decision tree (DT) algorithms.…”
Section: Introductionmentioning
confidence: 99%